A review of flexible lithium-sulfur and analogous alkali metal-chalcogen rechargeable batteries - Peng, Hong-Jie; Huang, Jia-Qi; Zhang, Qiang (Chemical Society reviews, 2017)
Flexible energy storage systems are imperative for emerging flexible devices that are revolutionizing our life. Lithium-ion batteries, the current main power sources, are gradually approaching their theoretical limitation in terms of energy density. Therefore, alternative battery chemistries are urgently required for next-generation flexible power sources with high energy densities, low cost, and inherent safety. Flexible lithium-sulfur (Li-S) batteries and analogous flexible alkali metal-chalcogen batteries are of paramount interest owing to their high energy densities endowed by multielectron chemistry. In this review, we summarized the recent progress of flexible Li-S and analogous batteries. A brief introduction to flexible energy storage systems and general Li-S batteries has been provided first. Progress in flexible materials for flexible Li-S batteries are reviewed subsequently, with a detailed classification of flexible sulfur cathodes as those based on carbonaceous ( e.g. , carbon nanotubes, graphene, and carbonized polymers) and composite (polymers and inorganics) materials and an overview of flexible lithium anodes and flexible solid-state electrolytes. Advancements in other flexible alkali metal-chalcogen batteries are then introduced. In the next part, we emphasize the importance of cell packaging and flexibility evaluation, and two special flexible battery prototypes of foldable and cable-type Li-S batteries are highlighted. In the end, existing challenges and future development of flexible Li-S and analogous alkali metal-chalcogen batteries are summarized and prospected. This review summarizes recent progress in flexible Li-S and analogous alkali metal-chalcogen batteries, including flexible chalcogen cathodes, flexible alkali metal anodes, flexible solid-state electrolytes, and flexible battery prototypes.